Research on Digital Huishan Clay Figures - Jiang, Hui; Joneurairatana, Eakachat (Asian Journal of Arts and Culture, 2025)
Huishan clay figures originated from the representative of Chinese clay figures and have a history of more than two programminghundred years. However, with the development of society and economy, the traditional handicraft of Huishan Clay Figure is gradually facing extinction. Nowadays, with the rapid development of information technology, digital technology has been applied to the study of intangible cultural heritage as a kind of efficient technical means, which plays an important role in the field of cultural inheritance and design innovation. This thesis will take Huishan clay figures as a research sample, and through the innovative design thinking process of carrying out computer-aided craft research, it will propose the strategy of digital craft to provide new ideas for realizing the inheritance and development of traditional craft in modern manufacturing, and lay the foundation for further integrating design and innovation, and developing highly personalized and customized new materials, new structures and new forms.